1996
DOI: 10.1210/endo.137.11.8895333
|View full text |Cite
|
Sign up to set email alerts
|

Lowering glucose depletes a thapsigargin-sensitive calcium pool and inhibits transcription of the S14 gene.

Abstract: S14 is a nuclear protein that is rapidly and synergistically induced by glucose and thyroid hormone, and the level of it's messenger RNA correlates with hepatocyte and adipocyte lipogenesis. We previously reported that the calcium ionophore A23187 markedly inhibits the carbohydrate response of the S14 gene without inhibiting glucose metabolism. Because the calcium ionophore not only increased intracellular cytosolic free calcium but also depletes intracellular calcium stores, we examined which of these two pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Results from the present study provide insight into the functional complexity of the relationship between Ca 2+ and the long‐term release, storage and production of GTH‐II protein, as well as GTH‐II‐ β mRNA levels. Depletion of Ca 2+ in Tg‐sensitive stores caused the emptying of stored GTH‐II and a decrease in GTH‐II‐ β mRNA levels at 12 h and 24 h. Similar to the present study, Tg has also been reported to reduce the transcription of the glucose‐sensitive S14 gene in hepatocytes (58). It is thus tempting to attribute the long‐term decrease in cellular GTH‐II content observed following Tg treatment to its effect on GTH‐II‐ β mRNA levels and a drop in protein synthesis.…”
Section: Discussionsupporting
confidence: 88%
“…Results from the present study provide insight into the functional complexity of the relationship between Ca 2+ and the long‐term release, storage and production of GTH‐II protein, as well as GTH‐II‐ β mRNA levels. Depletion of Ca 2+ in Tg‐sensitive stores caused the emptying of stored GTH‐II and a decrease in GTH‐II‐ β mRNA levels at 12 h and 24 h. Similar to the present study, Tg has also been reported to reduce the transcription of the glucose‐sensitive S14 gene in hepatocytes (58). It is thus tempting to attribute the long‐term decrease in cellular GTH‐II content observed following Tg treatment to its effect on GTH‐II‐ β mRNA levels and a drop in protein synthesis.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the status of Ca 2 + pools can influence the expression of genes involved in regulating cell growth, and the activity of growth-regulating genes in turn can influence the size and status of endoplasmic reticulum Ca 2 + pools. In recent years, other instances of either activation [108] or inhibition [109] of gene expression clearly linked to depletion of endoplasmic reticulum Ca 2 + have been reported. These findings raise the general question of the role of intracellular Ca 2 + storage in the response to other Ca 2 + -mobilizing stimuli, whether pharmacological (ionophores, SERCA inhibitors) or physiological (phospholipase C-linked agonists).…”
Section: Endoplasmic Reticulum Calcium Stores Can Regulate Gene Exprementioning
confidence: 99%
“…The precise identity of the accessory factor for the S14 CHORE has yet to be established. The effect of carbohydrate on S14 gene regulation involves both protein phosphorylation (51), and the maintenance of a specific intracellular calcium pool that signals for reduced transcription (52), indicating further complexity of the regulatory system.…”
Section: Long-chain Fatty Acidsmentioning
confidence: 99%
“…Work described from the authors' laboratory was supported by NIH grant (to W.B.K.). Mariash C 1996 Insulin increases the processing efficiency of messenger ribonucleic acid-S14 nuclear precursor. Opposing effects of glucagon and triiodothyronine on hepatic levels of messenger ribonucleic acid S14 and the dependence of such effects on circadian factors.…”
Section: Acknowledgmentsmentioning
confidence: 99%